The metaphor of the magnetized rings and the Platonic interpretation of the State unity - Aguirre-Santos, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Traditionally, the metaphor of the magnetized rings contained in the Socratic monologue of platonic Ion has been interpreted epistemologically, in a context of debate on the nature of the poetic activity. Without denying this aspect, the interpretation defended in this paper is that by means of the metaphor of magnetized rings are confronted two opposite ways of understanding the unity of the State: one, which is established by the political téchne, of a rational, autonomous, differentiated and permanent nature; and the other one, defended by poets and rhapsodists, of an irrational, heteronomous, homogenizing and liturgical nature.